Thermoelectrics for Power Generation - A Look at Trends in the Technology 2016
DOI: 10.5772/66086
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Antimony-Telluride: From First-Principles Calculations to Thermoelectric Applications

Abstract: Silver-antimony-telluride (AgSbTe 2 ) based compounds have emerged as a promising class of materials for thermoelectric (TE) power generation at the mid-temperature range. This Chapter demonstrates utilization of irst-principles calculations for predicting TE properties of AgSbTe 2 -based compounds and experimental validations. Predictive calculations of the efects of La-doping on vibrational and electronic properties of AgSbTe 2 compounds are performed applying the density functional theory (DFT), and tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 100 publications
1
7
0
Order By: Relevance
“…This was predicted from first-principles calculations of TE transport coefficients, applying Boltzmann transport theory, implemented for three model compounds, namely, Ag 3 SbTe 4 , AgSb 3 Te 4 , and AgSbTe 2 , exhibiting Sb/Ag ratios of 1/3, 3, and 1, respectively. It was shown that the increase in the Sb/Ag ratio results in a decrease in electrical conductivity simultaneously with an increase in the Seebeck coefficient for a wide temperature range from 50 through 1000 K . This trend is corroborated by the data recorded in Table and Figure b,c and corresponds to the results presented in the study of Jovovic and Heremans, who reported a decrease in both Seebeck coefficient and resistivity owing to the addition of 2% AgTe to a stoichiometric AgSbTe 2 -phase, that is, a reduction in the Sb/Ag ratio.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This was predicted from first-principles calculations of TE transport coefficients, applying Boltzmann transport theory, implemented for three model compounds, namely, Ag 3 SbTe 4 , AgSb 3 Te 4 , and AgSbTe 2 , exhibiting Sb/Ag ratios of 1/3, 3, and 1, respectively. It was shown that the increase in the Sb/Ag ratio results in a decrease in electrical conductivity simultaneously with an increase in the Seebeck coefficient for a wide temperature range from 50 through 1000 K . This trend is corroborated by the data recorded in Table and Figure b,c and corresponds to the results presented in the study of Jovovic and Heremans, who reported a decrease in both Seebeck coefficient and resistivity owing to the addition of 2% AgTe to a stoichiometric AgSbTe 2 -phase, that is, a reduction in the Sb/Ag ratio.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, there is a certain orientation relationship between the matrix and the precipitates as shown in Figure 7, which suggests that these precipitates are endotaxially embedded in the matrix exhibiting interfacial free-energy values as low as approximately 200 mJ m −2 . 25 Detection of such endotaxially embedded precipitates has already been demonstrated for a AgSbTe−PbTe alloy using HRTEM. 56 4.2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations